Salicylate induces reactive oxygen species and reduces ultraviolet C susceptibility in Staphylococcus aureus. Issue 8 (13th March 2018) - Cai, Jia-Yi; Wang, Yuan-yuan; Ma, Kai; Hou, Yong-Na; Yao, Guo-Dong; Hayashi, Toshihiko; Itoh, Kikuji; Tashiro, Shin-ichi; Onodera, Satoshi; Ikejima, Takashi
Abstract: This study demonstrates that growth of Staphylococcus aureus in the presence of salicylate reduces ultraviolet C (UVC)-induced cell death and increases the generation of reactive oxygen species (ROS). In addition, compounds that scavenge ROS (N-acetylcysteine, glutathione, catalase and superoxide dismutase) reverse the increased UVC survival induced by growth in the presence of salicylate, while ROS donors (tert-butylhydroperoxide, H2 O2 and NaClO) enhance survival of salicylate challenged cultures. Collectively, these findings suggest that ROS production induced by growth in the presence of salicylate protects S. aureus from UVC-induced cell death. Abstract : Salicylate induces resistance of S. aureus to UVC via generation of ROS.